PREPARATION OF HIGH PERFORMANCE ACTIVATED CHARCOAL FROM RICE STRAW FOR COSMETIC AND PHARMACEUTICAL APPLICATIONS - Pattananandecha, Thanawat; Ramangkoon, Sumontha; Sirithunyalug, Busaban; Tinoi, Jidapa; Saenjum, Chalermpong (International Journal of Applied Pharmaceutics, 2019)
Objective: Rice straw is an agricultural waste material which has a negative impact on the environmental. This study's aim was to prepare high-performance rice straw activated charcoal (RSAC) for cosmetic and pharmaceutical applications using chemical activation technique. Methods: Three cultivars of rice straw namely Dok Mali 105 (DM105), RD6 and Niaw San-Pah-Tawng were selected to determine the lignin content. The rice straw with the highest lignin content was selected to produce rice straw activated charcoal. The particle of size 20, 40 and 60 mesh was carbonized at 200, 300, 400, 500 and 600 °C for 1, 2, and 3 h. The obtained charcoal with the highest iodine number was then refluxed using potassium hydroxide and phosphoric acid as an activating agent in the ratios of 1:10 w/v at 70, 80, 90, and 100 °C for 2 (KOH) and 3 (H3PO4) h. The adsorption ability on iodine, methylene blue, acetaminophen, and aflatoxin B1 was investigated. Additionally, pore structure, pore size, and surface area were also determined relative to medical-grade activated charcoal. Results: DM105 rice straw contains the highest amount of lignin with 24.3 %w/w, followed by RD6 and Niaw San-Pah-Tawng, respectively. DM105 rice straw with particle size 60 mesh carbonized at 400 °C for 2 h (DM60T400H2) demonstrated the highest iodine number. The activation step of DM60T400H2 using 1:10 w/v potassium hydroxide at 70 and 80 °C for 2 h exhibited the highest iodine, methylene blue, acetaminophen, and aflatoxin B1 adsorption capacity. The scanning electron microscope (SEM) image and Brunauer-Emmett-Teller (BET) showed the microporous structure of obtained RSAC. Conclusion: RSAC prepared from rice straw of DM105 has potential in cosmetic or pharmaceutical applications.